SRAP MARKERS FOR FLOWER STALK COLOR IN CHINESE KALE - J. J. Yuan; H. C. Liu; S. W. Song; G. W. Sun; R. Y. Chen (Journal of Animal and Plant Sciences, 2015)
Chinese kale is avegetables native to south China. The flower stalk, the edible part of this plant, has a high nutrition value. Flower stalk color is one of the most important factorsof the quality of Chinese kale. In this study, a bulked segregate analysis (BSA) was used to identify sequence-related amplified polymorphism (SRAP) markers associated with the flower stalk color in Chinese kale(Brassica alboglabra Bailey). A segregating F2population consisting of 196 plants derived from a cross of cv. Zhonghua (green flower stalk) and cv. Hongjiao (mauve flower stalk) was used. A total of 153 pairs of SRAP primers were used to amplify the DNA of the cv. Hongjiao and cv. Zhonghua, and investigate the DNA pools of their mauve and green flower stalk, respectively. Twenty-nine of the primers pairs obtained different bands. The DNA pools of the mauve and green flower stalk were successfully amplified. Only the pair of me2/em14 consistently exhibited different bands in all 29 pairs of primers. The amplification results of the individual plantsin the DNA pools and F2 generation indicated that me2/em14 was the molecular marker associated with the flower stalk color in Chinese kale.
Keywords: Brassica alboglabra; SRAP marker; color of flower stalk